The Effectiveness Of The Flipped Classroom Type Blended Learning Model In Basic Graphic Design Subjects at Vocational High School - Akbar Haris Sunarya; Rosihan Ariyuana; Yusfia Hafid Aristyagama (Pendidikan Teknik Informatika dan Komputer, Universitas Sebelas Maret, 2023)
This study aims to determine the differences in student learning outcomes in the application of blended learning the flipped classroom model to the direct learning model and also to determine the more effective learning model between blended learning type flipped classroom with direct learning model. This study uses a quantitative approach with a quasi-experimental design and uses a pretest-posttest control. The population of this research is all students of class X majoring in Multimedia. The sample used is 54 students. The sampling technique in this research is using the total sampling method. Data obtained from the results of pre-test and post-test based on indicators of student learning outcomes.The results obtained from this study are as follows. First, there are differences in learning outcomes in Basic Graphic Design subjects in the experimental class by applying the blended learning type flipped classroom and the control class applying the direct learning model. It is proven by the average learning outcomes of the experimental class of 77.-3 and the control class of 73.14. The second is that the blended learning model of the flipped classroom type is more effective than the direct learning model. The results of the effectiveness behavior in the experimental class with the application of the flipped classroom blended learning model are in the medium category, while the control class with the direct learning model is in the low category.